2023
DOI: 10.1021/jacs.3c01681
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of AS2077715 and Funiculosin: Pathway Reconstitution and Identification of Enzymes that Form the All-cis Cyclopentanetetraol Moiety

Abstract: The complete biosynthetic pathways of the potent antifungals AS2077715 (1) and funiculosin (2) are reconstituted and characterized. A five-enzyme cascade, including a multifunctional flavin-dependent monooxygenease and a repurposed Omethyltransferase, is involved to perform the dearomatization, stereoselective ring contraction, and redox transformations to morph a hydroxyphenyl-containing precursor into the unusual all-cis cyclopentanetetraol moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Enzymatic ring contraction in conjugated benzene systems is rare, exemplified by the ferredoxin-like protein AlpJ in kinamycin biosynthesis (Streptomyces ambofaciens) (Figure S65A) and the collaboration between a flavin-dependent monooxygenase (FMO) with a repurposed O -methyltransferase (OMT) in AS2077715 biosynthesis (Talaromyces coalescens) (Figure S65B). The annotation of BGC pci56 revealed five unique genes compared to its highly homologous agnPKS . These five genes encode two FMOs (Pci56F and Pci56J), a MT (Pc56D), a TF (Pc56H), and an MFS (Pc56G) (Figure S66).…”
Section: Resultsmentioning
confidence: 99%
“…Enzymatic ring contraction in conjugated benzene systems is rare, exemplified by the ferredoxin-like protein AlpJ in kinamycin biosynthesis (Streptomyces ambofaciens) (Figure S65A) and the collaboration between a flavin-dependent monooxygenase (FMO) with a repurposed O -methyltransferase (OMT) in AS2077715 biosynthesis (Talaromyces coalescens) (Figure S65B). The annotation of BGC pci56 revealed five unique genes compared to its highly homologous agnPKS . These five genes encode two FMOs (Pci56F and Pci56J), a MT (Pc56D), a TF (Pc56H), and an MFS (Pc56G) (Figure S66).…”
Section: Resultsmentioning
confidence: 99%
“…Biosynthetic studies have revealed the enzymes involved in the formation of the cyclopentanetetraol moiety of AS2077715 23 , a fungal natural product from Capnodium species 339855. 21 A series of flavin-dependent monooxygenases and an O -methyltransferase convert a hydroxyphenyl motif to the all- cis cyclopentanetetraol via dearomatisation, ring contraction and redox reactions.…”
mentioning
confidence: 99%